Assessment of Nurses’ Knowledge and Practice Regarding Surgical Site Infection Prevention and Influencing Factors - Iqbal, Bushra; Ashraf, Aneela (Biological and Clinical Sciences Research Journal, 2025)
Surgical site infections (SSIs) are among the most common healthcare-associated infections and are largely preventable. Nurses play a crucial role in perioperative care, and their knowledge and practices significantly influence SSI prevention. However, in developing countries like Pakistan, compliance with evidence-based infection control measures remains a challenge. Objective: To assess the knowledge and practices of nurses regarding surgical site infection (SSI) prevention and identify factors affecting their compliance. Methods: This cross-sectional study was conducted in the Department of Nursing at Nishtar Hospital, Multan, from March 2024 to March 2025. A total of 100 nurses involved in postoperative patient care in surgical wards and outpatient departments were selected through non-probability sampling. Data were collected using a structured questionnaire consisting of 12 multiple-choice knowledge questions based on international infection control guidelines, and 12 practice-based Likert-scale items (1 = never, 3 = always). Data were analyzed using SPSS version 25. Logistic regression was applied to identify factors associated with good knowledge and practice, with odds ratios (OR) and 95% confidence intervals (CI) calculated. A p-value < 0.05 was considered statistically significant. Results: The mean knowledge score among participants was 6.23 ± 1.5. Overall, 40 nurses (40%) demonstrated good knowledge (95% CI: 35.2–44.5). Male nurses were significantly more likely to have good knowledge (OR: 3.18; 95% CI: 2.12–5.01), as were nurses with ≥5 years of experience and prior SSI training (OR: 1.89; 95% CI: 1.33–3.01). Conversely, lack of training was associated with reduced knowledge (OR: 1.76; 95% CI: 1.08–2.88). Regarding practice, 47 nurses (47%) demonstrated good compliance with SSI prevention measures (95% CI: 42.5–52.3). Female nurses (OR: 2.42; 95% CI: 1.61–3.47), those aged ≥30 years (OR: 1.81; 95% CI: 1.12–3.03), and diploma holders (OR: 2.30; 95% CI: 1.12–4.83) were significantly more likely to exhibit good practices compared to their counterparts. Conclusion: The findings reveal suboptimal knowledge and practices among nurses regarding SSI prevention. Structured training programs, continuous professional development, and reinforcement of updated evidence-based guidelines are essential to improve infection control practices and surgical outcomes in Pakistani hospitals.